Study of MicroRNA-192 as an Early Biomarker for Diagnosis of Diabetic Nephropathy - Mohamad Motawea; Mayada S. Khalel; Ismail Kandil; Ahmed Mohsen Faheem; Maysaa El Sayed Zaki; Mostafa Abdelsalam; Fady Kyrillos (Diagnostics, 2025)
Background/Objectives: Diabetic nephropathy (DN) is a serious complication of diabetes mellitus. This clinical condition is diagnosed through the detection of microalbuminuria. Molecular biomarkers such as MicroRNA-192 may play a role in the early diagnosis of this condition. This study aims to compare the serum concentrations of MicroRNA-192 in diabetic patients with and without DN and in healthy individuals. Methods: This study was a retrospective case-control study that included three groups. Group I included diabetic patients without DN, Group II included patients with DN, and Group III included healthy control subjects. Blood samples were obtained from each participant and subjected to a full biochemical study including creatinine, albumin, and the detection of MicroRNA-192 by real-time polymerase chain reaction. Results: There were significant differences among the MicroRNA-192 levels in the three groups (p-0.001). There was a significant increase in the MicroRNA-192 level in Group I (1.35 ± 7 0.5) compared with Group II (0.65 ± 7 0.2, p3 = 0.001) and Group III (0.83 ± 7 0.3, p1-0.001). There was a significant reduction in the MicroRNA-192 level in Group II compared with Group III (p2-0.001). Conclusions: This study highlights the potential role of serum miR-192 as a noninvasive biomarker for the early detection of DN in patients with type 2 DM. Our findings demonstrated that serum miR-192 levels were significantly reduced in patients with DN compared with diabetic patients without nephropathy and healthy controls, suggesting the possible protective role of miR-192 in early disease stages.